Cystatin C peptidomimetic derivative with antimicrobial properties as a potential compound against wound infections. Issue 4 (15th February 2017) - Pikuła, Michał; Smużyńska, Maria; Krzystyniak, Adam; Zieliński, Maciej; Langa, Paulina; Deptuła, Milena; Schumacher, Adriana; Łata, Jakub; Cichorek, Mirosława; Grubb, Anders; Trzonkowski, Piotr; Kasprzykowski, Franciszek; et al.
Graphical abstract: Abstract: A peptidomimetic called A20 (Cystapep 1) structurally based upon the N -terminal fragment of human cystatin C is known to have strong antibacterial properties. A20 is characterized by high activity against several bacterial strains often isolated from infected wounds, including methicillin-resistant S. aureus (MRSA). In this work we wanted to explore the therapeutic potential of A20 in the treatment of wound infections. We examined, cytotoxicity, allergenicity and impact of A20 on the proliferation and viability of human keratinocytes. Furthermore, the previously described antimicrobial action of A20 has been confirmed here with reference strains of bacteria and extended by several other species. The A20 was highly active against Gram-positive bacteria with minimal inhibitory (MIC) and minimal bactericidal concentrations (MBC) between 8 and 128 μg/mL. A20 did not affect proliferation of primary human keratinocytes in concentrations up to 50 μg/mL. At the same time, it did not activate Peripheral Blood Mononuclear Cells (PBMCs), including basophils or neutrophils in vitro . Interestingly A20 was found to display immunomodulatory functions as it influences the production of Th2 cytokines (IL-4 and IL-13) by activated PBMCs. It was also resistant to degradation for at least 48 h in human plasma. The results indicate that A20 is effective against the multiantibiotic-resistant bacteria and has a high safety profile, which makes it a promising antimicrobial drug candidate.